The Association Between Eating-Compensatory Behaviors and Affective Temperament in a Brazilian Population - Chapuis-de-Andrade, Sabrina; Moret-Tatay, Carmen; Costa, Dalton Breno; Abreu da Silva, Francielle; Irigaray, Tatiana Quarti; Lara, Diogo R. (Frontiers in Psychology, 2019)
Eating-compensatory behaviors are associated with biological and psychological complications, with high rates of morbidity and mortality. Different elements may contribute to the development of eating-compensatory behaviors, such as genetic, physiological, environmental and temperamental factors. Therefore, the aim of this study was to examine the association between affective temperaments and eating-compensatory behaviors. A sample of 27.501 volunteers, between 18 and 55 years old, mean age 28.9 ± 8.7 years (69.6% women), were assessed by the Brazilian Internet Study on Temperament and Psychopathology (BRAINSTEP). The results showed that eating-compensatory behaviors were associated with distinctive affective temperaments. Cyclothymic types were more associated with eating-compensatory behaviors. The avoidant and irritable types presented lower percentages of eating-compensatory behaviors in women and men, respectively. In conclusion, this study highlighted that participants who adopted frequent eating-compensatory behaviors are more likely to have dysfunctional affective traits. Consequently, the affective temperaments should be considered as a strategy to build capacity for prevention, treatment, and care of eating-compensatory behaviors.